Community diagnosis of occupational health problems according to informal sector actors working in the city of Ouagadougou in 2024, Burkina Faso - Kaboré, Ahmed; Pitroipa, Edna Marie Marguerite; Ramdé, Pingdwindé Aristide; Yaméogo, Aristide Relwende; Soubyabiga, Rayendé Juste Romaric; Gumedzoe–Hoseto, Grâce-Alice Enam Bladavi; Yaméogo, Nobila Valentin; Méda, Nicolas (International Journal of Occupational Safety and Health, 2026)
Introduction: Occupational health promotes physical, mental and social well-being of all workers in their jobs. In Burkina Faso, however, it hardly covers the informal sector. The study aimed to analyze the occupational health problems perceived by informal sector workers in the city of Ouagadougou in 2024. Methods: We conducted an exploratory qualitative cross-sectional study through semi-structured individual interviews using an interview guide. It included workers of informal sector coming from trade, services and industrial domains and managers of structures working with them. A thematic analysis was carried out using NVIVO 14 software. Results: Unhealthy working conditions, occupational hazards and inaccessibility to occupational health services were the problems cited by workers. Deficiency of knowledge on these risks, regulatory obligations and the use of personal protective equipment were cited as causes of occupational hazards. The causes of occupational health services inaccessibility were lack of information on these services, the lack of organization of the sector and the focus on the formal sector. The solutions proposed were legal, medical and technical. Conclusion: Informal workers are confronted to a range of health problems. Their needs should be highlighted in the country’s occupational health and social protection policies and strategies.